Investigating sex disparity in a national cohort of patients undergoing kidney replacement therapy in South Africa - Motlhobogwa, Kutlo; Manning, Kathryn; Davids, Mogamat Razeen; Muller, Elmi; du Toit, Tinus (African Journal of Nephrology, 2024)
Background: Sex disparity in kidney replacement therapy has been extensively studied globally. However, the situation in Africa, particularly in South Africa, remains poorly understood. This study aims to fill this knowledge gapby recording a comprehensive analysis of prevalent and incident KRT patients in South Africa, shedding light onpotential disparities between the sexes. Methods: This retrospective cohort study used data from the national kidney replacement therapy registry, to examine potential sex disparities. We analysed prevalence data on 31 December 2017 and incidence data from 1 January 2013 to 31 December 2017. Specifically, we calculated sex-specific prevalence, annual incidence, and cumulative incidence per million population (pmp), to gain insights into the patterns and trends related to kidney replacement therapy among the sexes. Results: On 31 December 2017, 10 745 patients with a median age of 52.6 years (interquartile range 41.8–62.3 years) years were receiving KRT, of whom 40.4% were women. A significantly lower proportion of women received KRT than men (148.7 vs 229.4 pmp; P = 0.001). On further analysis, the KRT prevalence in men and women was 73.9 and 56.3 pmp in the public sector, and 1 112.0 and 613.5 pmp in the private sector. The proportion of preemptive transplants (8.6% vs 8.2%), overall transplants (17.2% vs 17.7%), treatment discontinuation (8.3% vs 8.9%)and death (53.0% vs 53.3%) were comparable between men and women. There was a clear de-escalating trend in the incidence of KRT over the 5-year study period for both sexes. Conclusion: A sex-specific disparity in KRT prevalence was observed, reflecting higher rates of KRT in male compared to females except transplant. This may suggest socio-cultural or socio-economic bias, but impact of biological factors cannot be excluded.